The association of -799C/T and -381A/G matrix metalloproteinase 8 (MMP-8) gene polymorphisms with periodontitis and active MMP-8 levels in the oral cavity - Fragkioudakis Ioannis; Ntolkeras Antonis; Kottaridi Christina; Grigoriadis Andreas; Sakellari Dimitra (Balkan Stomatological Society, 2023)
Background/Aim: To investigate the relationship of the -799C/T (rs11225395) and -381A/G (rs1320632) matrix metalloproteinase 8 (MMP8) gene polymorphisms with periodontitis and the levels of active MMP-8 (aMMP-8) in an oral rinse. Material and Methods: Eighty subjects that had participated in a previous study contributed with an oral rinse sample collected before full-mouth periodontal clinical assessments. In addition, aMMP-8 levels in an oral rinse were quantified with a chairside point of care (PoC) test (PerioSafe), and the accompanying digital reader (OraLyzer). After DNA extraction, the samples were amplified with Polymerase Chain Reaction using specific primers. The amplified DNA samples were analyzed with a sequencing assay. Results: All of the patients were homozygous for the -381A/A genotype while 21.2% of the subjects were homozygous for the -799T/T genotype. No significant association was found between the -799T/T and periodontal disease, however, the presence of the specific genotype was significantly associated with the stage of periodontitis and the levels of aMMP-8 in the oral cavity. Conclusions: The results of the current study of 80 Greek subjects indicated that the presence of the rs11225395 (-799 T/T) genotype may be correlated with the severity of the periodontal disease. In addition, patients homozygous for the T/T genotype had higher levels of aMMP-8.